PERSEPSI SISWA TERHADAP PERAN GURU PPKn DALAM PEMBENTUKAN KARAKTER MANDIRI BELAJAR DI SMAN 1 KAMPAR TIMUR KECAMATAN KAMPA KABUPATEN KAMPAR - Rara Rana Selvia; Hambali Hambali; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is background by the fact b importance of character education in the school environment. With the current 2013 curriculum, students are required to have good character, with that character education is needed, one of which is an independent character when studying. The formulation of the research problem is How Students' Perceptions of the Role of PPKn Teachers in the Formation of Independent Learning Characters in SMAN 1 Kampar Timur, Kampa District, Kampar Regency. The research objective was to see the Students' Perceptions of the Role of PPKn Teachers in Self-Learning Character Building in SMAN 1 Kampar Timur, Kampa District, Kampar Regency. According to Law No. 14 of 2005 concerning Teachers and Lecturers that teachers are professional educators with the main task of educating, teaching, guiding, training, training, ass,essing, and students in early childhood education, basic education, and secondary education. This research method is descriptive quantitative, the data techniques used in this study are questionnaires,interviews, and documentation. The research variable is the role of the PPKn teacher in ordering the independent learning character which consists of 4 indicators with a total of 20 questions based on the Research Instrument. The population in this study were students of SMAN 1 Kampar Timur. The sample in this study was taken using a purposive sampling technique. Based on the results of research and recapitulation that has been done by researchers. Respondents who answered Very often (SS) + Often (S) 29.26% + 41.96% = 71.22%. Based on the recapitulation, it can be stated that the students' perceptions of the role of the PPKn teacher in the formation of independent learning character at SMAN 1 Kampar Timur, Kampa District, Kampar district are in the